2021
DOI: 10.1017/cts.2021.16
|View full text |Cite
|
Sign up to set email alerts
|

Professional and personal impact of the COVID-19 pandemic restrictions on non-COVID-19-related clinical research

Abstract: This version may be subject to change during the production process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…These data confirm earlier institutional and CTSA-wide surveys and are not surprising, given the widespread mandated restrictions on non-COVID-related clinical research early in the pandemic [24,68]. Additional common reasons for decreased activity reported in this and previous surveys include concerns for the safety of research participants, investigators, and staff, and staffing shortages.…”
Section: Discussionsupporting
confidence: 86%
“…These data confirm earlier institutional and CTSA-wide surveys and are not surprising, given the widespread mandated restrictions on non-COVID-related clinical research early in the pandemic [24,68]. Additional common reasons for decreased activity reported in this and previous surveys include concerns for the safety of research participants, investigators, and staff, and staffing shortages.…”
Section: Discussionsupporting
confidence: 86%
“…Women generally carry greater responsibility in childcare than men 23 but some research has suggested that the pandemic has impacted mothers and fathers with children younger than 18 equally. 24 The pandemic may have increased the amount of time postdoctoral fellows and faculty have available for writing 7,25 but women have submitted fewer manuscripts for publication, 20,26 submitted fewer firstauthored papers, and published less than in 2019. 27 Research by the NIH indicates that extramural researchers who identify as Black or African American showed less concern about the negative impact of the pandemic on their career trajectory, were more likely to state they had organizational support, and reported no difference compared with White peers in job productivity or the impact of caretaking responsibilities on productivity.…”
Section: Discussionmentioning
confidence: 99%
“…Women generally carry greater responsibility in childcare than men 23 but some research has suggested that the pandemic has impacted mothers and fathers with children younger than 18 equally. 24 The pandemic may have increased the amount of time postdoctoral fellows and faculty have available for writing 7,25 but women have submitted fewer manuscripts for publication, 20,26 submitted fewer first-authored papers, and published less than in 2019. 27…”
Section: Discussionmentioning
confidence: 99%
“…While some participants found it easier to access and engage with researchers virtually, others found it difficult due to external stressors and other commitments. (Melvin et al, 2021 ) Study staff likewise needed to balance clinical and research priorities alongside home life and caretaking responsibilities exacerbated by the pandemic (Gilmartin et al, 2020 ). Furthermore, participants and researchers both experienced a learning curve adapting to virtual approaches that were sometimes novel (Loucks et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%